2018
DOI: 10.1016/j.scitotenv.2018.01.129
|View full text |Cite
|
Sign up to set email alerts
|

Feedbacks between soil penetration resistance, root architecture and water uptake limit water accessibility and crop growth – A vicious circle

Abstract: Water is the most limiting resource for global crop production. The projected increase of dry spells due to climate change will further increase the problem of water limited crop yields. Besides low water abundance and availability, water limitations also occur due to restricted water accessibility. Soil penetration resistance, which is largely influenced by soil moisture, is the major soil property regulating root elongation and water accessibility. Until now the interactions between soil penetration resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
116
0
13

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(135 citation statements)
references
References 45 publications
6
116
0
13
Order By: Relevance
“…Soil penetration resistance is positively correlated with soil bulk density and the absolute value of the soil matric potential (Gao et al, 2012; Whalley et al, 2007). Higher soil penetration resistance leads to lower root growth rates and in consequence to less extended root systems with reduced ability to take up water from deeper soil layers (Bengough et al, 2011; Chen et al, 2014; Colombi et al, 2018; Tracy et al, 2012; Valentine et al, 2012). This is an issue in particular during prolonged dry spells when the upper soil layers are water depleted and when the subsoil water supply has high potential value for plant transpiration (Gaiser et al, 2013; Kirkegaard et al, 2007).…”
mentioning
confidence: 99%
“…Soil penetration resistance is positively correlated with soil bulk density and the absolute value of the soil matric potential (Gao et al, 2012; Whalley et al, 2007). Higher soil penetration resistance leads to lower root growth rates and in consequence to less extended root systems with reduced ability to take up water from deeper soil layers (Bengough et al, 2011; Chen et al, 2014; Colombi et al, 2018; Tracy et al, 2012; Valentine et al, 2012). This is an issue in particular during prolonged dry spells when the upper soil layers are water depleted and when the subsoil water supply has high potential value for plant transpiration (Gaiser et al, 2013; Kirkegaard et al, 2007).…”
mentioning
confidence: 99%
“…Recently it was reported that the contribution of aboveground litter to soil organic carbon content might exceed that of roots. This is due to higher decomposability of aboveground residues compared to roots, resulting in more microbial by-products and eventually higher amounts of longterm stabilized soil organic carbon (Cotrufo et al, 2013(Cotrufo et al, , 2015Lavallee et al, 2018). However, numerous other studies showed that 60 %-70 % of soil organic carbon in arable soil is derived from roots, suggesting that roots are the dominant input source for soil organic carbon (Balesdent and Balabane, 1996;Kätterer et al, 2011;Kong and Six, 2010;Rasse et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Soil structure and associated soil physical properties are greatly affected by soil management. Tillage has been shown to improve penetrability and aeration of the topsoil (Colombi et al, 2018;Dal Ferro et al, 2014;Martínez et al, 2016a, b;Schjonning and Rasmussen, 2000). However, long-term tillage can also lead to decreased gas transport capability and high penetration resistance in both the topsoil (Kahlon et al, 2013) and the subsoil (Martínez et al, 2016a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Soil bulk density and penetration resistance are the major soil properties regulating plant root elongation, water accessibility and plant productivity (Colombi et al, 2018). Optimum topsoil conditions for plant root growth in a sandy clay loam and clay loam are <1.40 Mg m -3 and penetration resistance -<1.5 MPa.…”
Section: Figurementioning
confidence: 99%